Pengungkapan Corporate Sosial Responsibility, Media Exposure dan Profitabilitas - Saraswati, Erwin; Nindi Febryanti, Upik; Sagitaputri, Ananda (E-Jurnal Akuntansi; Vol 30 No 12 (2020)DO - 10.24843/EJA.2020.v30.i12.p17, 2020)
This research examined the impact of corporate social responsibility (CSR) disclosure on firms’ profitability moderated by media exposure. The samples selected were 15 agricultural firms listed on Indonesian Stock Exchange for the period of 2016-2018. The data were analyzed using Moderated Regression Analysis (MRA). The result showed that CSR disclosure do not affect ROA, but media exposure had a direct effect to ROA. Based on the legitimacy theory, firms conduct CSR to align with societal values and norms. To earn legitimacy from the society, CSR needs to be communicated to channels that are easily accessed by the people, so the benefits of CSR can be realized into profits. Based on the research results, companies are expected to use their websites or social media more often to communicate their CSR activities.   Keywords: Corporate Sosial Responsibility; Disclosure; Profitability; Media Exposure.